/
/
/
Find the value of the expression for the given replacement value.
Not my Question
Flag Content

# Question : Find the value of the expression for the given replacement value. : 2163453

MULTIPLE CHOICE. Choose the one alternative that best completes the statement or answers the question.

Find the value of the expression for the given replacement value.

1) (x + 9/x - 8); x = 7

A) - (15/2)

B) - (1/16)

C) - 16

D) - (2/15)

2) (x - 7/-3x - 1); x = 4

A) (3/13)

B) (7/4)

C) (3/4)

D) (13/3)

3) (x2 - 10x + 5/x2 + 2x - 1); x = 3

A) - (8/7)

B) (22/7)

C) - 1

D) (8/7)

4) (a2/1 - a2); a = 9

A) - (81/80)

B) (81/82)

C) (81/80)

D) - (80/81)

Solve the problem.

5) A formula for the focal length of a lens is f = (ab/b + a) Calculate f (the focal length) for a = 8 cm and b = 11 cm. Round to the nearest tenth of a centimeter when necessary.

A) 4.0 cm

B) 4.6 cm

C) 3.4 cm

D) 5.5 cm

6) A gas law in chemistry says that (PV/T) = (pv/t). If T = 210, t = 290, V = 7, P = 90, and v = 6, find the value of p. Round to the nearest thousandth when necessary.

A) 0.5

B) 14.5

C) 145

D) 840

Find any numbers for which the rational expression is undefined.

7) (4/z - 7)

A) z = -7

B) z = 0

C) z = 7

D) none

8) (3/r + 8)

A) r = 0

B) r = -8

C) r = 8

D) none

9) (z - 5/7)

A) z = 0

B) z = -5

C) z = 5

D) none

10) (m - 6/4 - m)

A) m = 4

B) m = 4, m = 6

C) m = -4

D) none

11) (x3 + 16x/2x - 20)

A) x = -4, x = 0, x = 4

B) x = 0

C) x = 10

D) x = -10

12) (3y - 2/y2 - 64)

A) y = (2/3)

B) y = 8, y = -8

C) y = 8

D) y = 64

13) (x2 - 100/x2 + 12x + 27)

A) x = -3, x = -9

B) x = 0

C) x = 3, x = -9

D) x = 10, x = -10

14) (x2 - 9/x2 - 9x + 18)

A) x = 3, x = -3

B) x = 6, x = 3

C) x = 0

D) x = -6, x = -3

15) (9x2 - 4/8x - 32)

A) x = (2/3), x = - (2/3)

B) x = 4

C) x = 32

D) none

16) (x3 + 4x4/x2 + 9)

A) x = -3

B) x = -9

C) x = 0, x = - (1/4)

D) none

Simplify the expression.

17) (24k3/6k)

A) 4k2

B) 18k2

C) 4k

D) 18

18) ((y + 3)(y - 7)/(y - 7)(y + 9))

A) (2y - 7/2y + 2)

B) (y - 3/y - 9)

C) (y + 7/y + 2)

D) (y + 3/y + 9)

19) (-2x - 2y/x + y)

A) - (1/2)

B) 2

C) -2

D) (1/2)

20) (8 - m/m - 8)

A) -1

B) -m

C) 1

21) (3x + 2/12x2 + 17x + 6)

A) (3x/4x + 3)

B) (3x + 4/4x + 17)

C) (1/4x + 3)

D) (3x + 2/12x2 + 17x + 6)

22) (y2 + 10y + 16/y2 + 17y + 72)

A) (10y + 2/17y + 9)

B) - (y2 + 10y + 16/y2 + 17y + 72)

C) (10y + 16/17y + 72)

D) (y + 2/y + 9)

23) (-12x + 12y/-12y + 12x)

A) -12

B) 12

C) 1

D) -1

24) (3k - 9/6 - 2k)

A) 1

B) -1

C) (3/2)

D) - (3/2)

25) (4x2 - 21x + 27/x - 3)

A) (4x2 - 21x + 27/x - 3)

B) 4x - 9

C) 4x2 - 30

D) (1/x - 3)

26) (5x2 + 15x3/12x + 36x2)

A) (5 + 15x3/12x + 36)

B) (5/12)

C) (5x/12)

D) (5x2 + 15x3/12x + 36x2)

27) (a2 - ab + 9a - 9b/a + 9)

A) (1/a + 9)

B) a - 2b + 1

C) a - b

D) (a2 - ab + 9a - 9b/a + 9)

List four equivalent forms for the rational expression.

28) - (x - 2/x + 7)

A) (-(x - 2)/x - 7), (-x + 2/x + 7), (x - 2/-(x - 7)), (x - 2/-x - 7)

B) (-(x - 2)/x + 7), (-x + 2/x + 7), (x - 2/-(x + 7)), (x - 2/-x - 7)

C) (-(x + 2)/x + 7), (-x + 2/x + 7), (x + 2/-(x + 7)), (x - 2/-x - 7)

D) (-(x - 2)/x + 7), (-x + 2/x - 7), (x - 2/-(x - 7)), (x - 2/-x - 7)

29) - (7y - 2/y - 16)

A) (-(7y - 2)/y - 16), (-7y - 2/y - 16), (7y - 2/-(y - 16)), (7y - 2/-y + 16)

B) (-(7y - 2)/y - 16), (-7y + 2/y - 16), (7y - 2/-(y - 16)), (7y - 2/-y + 16)

C) (-(7y - 2)/y - 16), (-7y + 2/y - 16), (7y - 2/-(y - 16)), (7y - 2/-y - 16)

D) (-(7y - 2)/y - 16), (-7y - 2/y - 16), (7y - 2/-(y - 16)), (7y - 2/-y - 16)

## Solution 5 (1 Ratings )

Solved
Mathematics 2 Years Ago 212 Views